Intraocular Viral Communities Associated With Post-fever Retinitis - Kotakonda Arunasri (Frontiers Media S.A., 2021)
The virome of ocular fluids is naive. The results of this study highlight the virome in the vitreous fluid of the eye of individuals without any ocular infection and compare it with the virome of the vitreous fluid of individuals with retinitis. A total of 1,016,037 viral reads were generated from 25 vitreous fluid samples comprising control and post-fever retinitis (PFR) samples. The top 10 viral families in the vitreous fluids comprised of Myoviridae, Siphoviridae, Phycodnaviridae, Herpesviridae, Poxviridae, Iridoviridae, Podoviridae, Retroviridae, Baculoviridae, and Flaviviridae. Principal coordinate analysis and heat map analysis clearly discriminated the virome of the vitreous fluid of the controls from that of the PFR virome. The abundance of 10 viral genera increased significantly in the vitreous fluid virome of the post-fever retinitis group compared with the control group. Genus Lymphocryptovirus, comprising the human pathogen Epstein-Barr virus (EBV) that is also implicated in ocular infections was significantly abundant in eight out of the nine vitreous fluid viromes of post-fever retinitis group samples compared with the control viromes. Human viruses, such as Hepacivirus, Circovirus, and Kobuvirus, were also significantly increased in abundance in the vitreous fluid viromes of post-fever retinitis group samples compared with the control viromes. The Kyoto Encyclopedia of Genes and Genomes (KEGG) functional analysis and the network analysis depicted an increase in the immune response by the host in the post-fever retinitis group compared with the control group. All together, the results of the study indicate changes in the virome in the vitreous fluid of patients with the post-fever retinitis group compared to the control group.